Effects of Various Curing Conditions on Volume Stability of Magnesium Phosphate Cement. (30th January 2021) - Wu, Jie; Lai, Zhenyu; Deng, Qiubai; Liu, Mengliang
Abstract : Magnesium phosphate cement (MPC) is an excellent repair material for civil and road engineering, but its volume stability under various environmental conditions significantly influences these applications. In this study, the volume stability of MPC under different curing conditions (e.g., air, standard, and water curing) is investigated. Moreover, the phases, weight loss, microstructure, and pore structure of the samples have been determined by X-ray diffraction, thermogravimetry, scanning electron microscopy, and Brunnauer–Emmet–Teller method. The results show that MPC will shrink by 8 × 10 −4 under air-curing conditions. At the same time, MPC will expand by 9 × 10 −4 under water-curing and standard curing conditions, which means that curing conditions influence the volume stability of MPC. Not only that, compared with air-curing conditions, the compressive strength of MPC under standard curing and water-curing conditions will decrease by 30% and 60%, respectively, which implies that greater humidity will reduce the mechanical properties of the repair material. Therefore, air curing is the best curing condition for MPC. To get a better repair effect, the environment should be avoided as much as possible in a humid state. The microscopic analysis results show that the volume expansion of MPC is related to hydration products, and the volume shrinkage occurs owing to drying shrinkage caused by internal moisture evaporation.